(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Salicylaldehyde was react with 4-amino-2,3-dimethyl-1-phenyl-3-Pyrazoline-5-on to produce the novel Schiff base ligand 2,3-dimethyl-1-phenyl-4-salicylidene-3-pyrazoline-5-on (HL). A new complexes of VO(II), Cr(Ш), Zn(II), Cd(II), Hg(II) and UO2(II) with mixed ligands of bipyridyl and new shiff base ( 2,3-dimethyl-1-phenyl-4-salicylidene-3-pyrazoline-5-on) (HL) were prepared . All prepared compounds were identified by atomic absorption, FT.IR , UV-Visable spectra and molar conductivity. From the above data, the proposed molecular structure for VO(II) complex is squre pyramidal while (Zn(II), Cd(II), Hg(II)) and ( UO2(II),Cr(III)) complexes are forming tetrahedral and octahedral geometry respectively.